Internal investigations in the trial of corporations in Italy: the practical implication of their admissibility for trial purposes - Marco Alessandro Bartolucci (Revista Brasileira de Direito Processual Penal)
The paper conducts a comprehensive analysis of corporate criminal liability in Italy, with a specific focus on internal corporate investigations. After providing a brief overview of the Italian legal system concerning corporate criminal liability, the paper compares internal investigations conducted by companies with the Public Prosecutor's preliminary investigations, examining their respective strengths, weaknesses, and differences. Additionally, the research explores the admissibility of internal investigations during the preliminary investigation stage and in the negotiation process, specifying the inherent limitations and practical challenges in the absence of specific regulations on this matter.